(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
Seven varieties of wheat seeds, such as BARI Gom-25, BARI Gom-26, BARI Gom-27, BARI Gom-28, BARI Gom-29, BARI Gom-30 and Kanchan were studied to determine the prevalence of seedborne fungi and their effects on germinating seeds and seedlings. The seeds were categorized into apparently healthy seeds, black point seeds, and shriveled and undersized seeds. Variation in different parameters (viz.Grading, weight, purity percentage, germination and seedling growth) became evident among the varieties. Seed health test on blotters and agar plate method showed that the major fungi associated with healthy seeds and black point seeds were Alternaria alternata, A. triticina, Bipolaris sorokiniana, B. tetramera, Curvularia lunata, Fusarium spp., and species of Aspergillus. The incidence of B. sorokiniana increased with increasing severity of black point infection. Reduction in germination, seedling emergence, plant stand, root and shoot growth, and vigor index were directly related with the severity of black point. Aspergillus spp. were seen more frequently associated with non-germinated seeds. J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(1): 33-48